Spiritualitas Performatif: Kritik dan Reorientasi Pelayanan Menuju Teologi Oikos - Surati, Susi Cicilya; Poluan, Agnes Relly (AISTHETIKOS Jurnal Ilmu Teologi dan Seni, 2026)
The ecclesiastical paradigm that measuresspirituality by the quantity of participation in ministry forces congregations toengage in “spiritual activism”. Paradoxically, despite efforts toseek external social validation, the internal quality of Oikosis neglected or replaced. With these limitations in mind, this article attempts to critique this phenomenon through a qualitative literature study with a contextual theological lens. The study confirms that this activism is a distortion of the meaning ofministry, whereby families act as ‘victims’ for the sake of institutional performance. As an alternative and solution, a theological reorientation is neededthat centres the family as the leader in faith formation.The function of the church as Ekklesia must move from the centre ofactivity to the centre of equipping that leads to spiritual life in thehome. The goal is to create authentic utilisation born inhealthy families, and the congregation can glorify God.